Mange skin diseases in dogs and cats in Jataí, Brazil: A retrospective study with notes on zoonotic aspects (Research, Society and Development, 2021)
The parasitic skin diseases, specifically mange diseases, are highly relevant in the animal health studies, due to a significant number of cases in the veterinary routine, beyond the importance in public health, due to zoonotic potential. Therefore, this study aimed report the occurrence of mange skin diseases with notes in the zoonotic potential from Jataí, Goiás, by an retrospective survey of mange cases diagnosed in dogs and cats treated at the Veterinary Hospital of the Federal University of Jataí. A total of 612 reports of parasitological tests, comprising cerumen swabs and skin scraping, were analyzed from January 2016 to December 2019. The most common causative mite in dogs was Demodex canis (10.94%), followed by Otodectes cynotis (2.92%), and Sarcoptes scabiei (2.54%). The most common causative mite in cats was Notoedres cati (20%), followed by O. cynotis (10%). These skin diseases are characterized as being highly contagious; therefore, these can be easily transmitted among animals and even humans. In addition, intense itching and skin lesions lead to discomfort, consequently causing stress to the animals. Thus, mite control as well as prompt diagnosis and treatment are relevant to manage these skin diseases and ensure animal welfare.